Oliver Wendell Holmes Jr. and legal logic - Kellogg, Frederic Rogers (Chicago : The University of Chicago Press, 2018)
With 'Oliver Wendell Holmes, Jr. and Legal Logic', Frederic R. Kellogg examines the early diaries, reading, and writings of Justice Oliver Wendell Holmes, Jr. (1841-1935) to assess his contribution to both legal logic and general logical theory.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 3, 2018).
Keywords: Holmes, Oliver Wendell, -- Jr., -- 1841-1935.; Law -- Philosophy; Law -- Methodology; Law; Laws of specific jurisdictions & specific areas of law